Criação e validação da Escala de autopercepção de capacidade para a dança (EACADA) para a população brasileira - CASTRO, Aila Maria Muribeca de (2024)
Objective: Create and validate the Self-Perceived Ability to Dance Scale (SPADS) for the Brazilian population. Methods: This is a questionnaire validation study carried out following the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) guidelines. Content, construct, structural validity and reliability were the clinimetric properties of the SPADS tested in the present study. The study included professional dancers, dance practitioners and/or dance students, who practiced dancing at least twice a week in the last 3 months, aged over 18 years. In addition to SPADS, the following instruments were applied: Self-Estimated Functional Inability because of Pain (SEFIP-dance) and the 36-Item Short Form Health Survey (SF-36). A subsample responded to the SPADS 7 days after the first completion, for reliability and internal consistency calculations. Results: Initially, ten experts in the field of sport and/or physical rehabilitation proposed 12 questions to measure the ability to dance. Secondly, experts were asked to give a score from 1 to 5 on the content and clarity for each of the 12 questions proposed in the first round. Thus, the content validity coefficient was calculated, without the need to exclude items (values ≥ 0.80). The SPADS was then applied to 100 dancers, the majority of whom were female, who practiced the dance modality more than 3 times a week and with a total practice time of more than 108 months. The dance modalities most practiced by the participants were: Classical Ballet, Urban Dances, Rhythms and Popular Dances. In structural validity, exploratory factor analysis identified unidimensionality with 12 items in the SPADS (Kaiser-Meyer-Olkin test = 0.81, p < 0.001 in Bartlett's test of sphericity, factor loadings >0.40). In construct validity, correlations were observed with the SF-36 and SEFIP-work domains, with correlation magnitude varying between 0.470 and 0.257, as expected according to our a priori hypothesis. Acceptable reliability (intraclass correlation coefficient = 0.85) and internal consistency (Cronbach's alpha = 0.89) were observed. No ceiling or floor effects were observed. Conclusion: SPADS presented adequate values and reliability and can be used to measure dance capacity in dancers.